High in-situ stress evaluation and disaster case analysis for the Sichuan–Tibet railway - DAI Xiangqian; WANG Chenghu; GAO Guiyun; YANG Xinshuai; LIU Jikun (Dizhi lixue xuebao, 2025)
Objective  The challenges posed by high in-situ stress along the newly constructed Sichuan–Tibet railway are significant, characterized by frequent catastrophic events such as rock bursts and large deformations in soft rocks, which substantially impact tunnel construction for the Sichuan–Tibet railway.   Method  Based on 366 sets of in-situ stress measurement data from the Yalin section of the Sichuan–Tibet railway and 28 documented cases of tunnel catastrophes in the areas along the Sichuan–Tibet railway, this study analyzes the characteristics of in-situ stress along the route, categorizes the catastrophic events, and evaluates the high in-situ stress conditions of the Sichuan–Tibet railway.   Results  In the B218, B219, and B222 stress divisions traversed by the Yalin section of the Sichuan–Tibet railway, the maximum (SH) and minimum (Sh) horizontal principal stresses increase with depth. Within a burial depth of 1000 m, SH and Sh range from 30.80–37.50 MPa and 21.40–23.56 MPa, respectively. At a burial depth of 2500 m, SH and Sh increase to 69.80–90.0 MPa and 48.40–56.56 MPa, respectively. The preferred orientations of SH are NWW, NW, and NE, consistent with focal mechanism solutions, albeit with some local deviations. The lateral pressure coefficient (kH/kh) is generally greater than 1, indicating that the Sichuan–Tibet railway is predominantly influenced by SH. Stress values in each stress division exhibit the pattern SH > SV > Sh, reflecting a strike-slip fault stress state in the deeper regions below 500 m burial depth. The stress accumulation level (μm) values for each stress division are concentrated around 0.3, suggesting a low regional stress accumulation level. Among the 28 documented tunnel catastrophe cases (12 involving rock bursts and 16 involving large deformations in soft rocks), the minimum burial depth for tunnels experiencing rock bursts is 700 m, while the minimum burial depth for tunnels experiencing large deformations in soft rocks is 275 m. Six tunnels are rated as under high stresses, and eight tunnels are rated as under extremely high stresses. High in-situ stress serves as the energy source and the fundamental cause of frequent catastrophes.   Conclusion  Through comparing the actual grades of tunnel disasters, the most appropriate criterion for predicting rock burst and large deformations in Sichuan–Tibet railway tunnels is determined after comparison and selection. Therefore, they should be prioritized in the studies for the subsequent construction of Sichuan–Tibet railway tunnels as a reference basis. [ Significance ] The research findings offer crucial evidence for the analysis of in-situ stress states and the prevention and control of high in-situ stress disasters in the regions along the Sichuan–Tibet railway, and possess significant engineering guiding significance for enhancing the safety of tunnel engineering and construction efficiency.